This website uses cookies to ensure you get the best experience.
By using this website, you agree to our Cookie Policy. Learn more

Algebra Cheat Sheet


Algebra Cheat Sheet

Number Rules

a\cdot 0=0 1\cdot a=a


Expand Rules

-(a\pm b)=-a\mp b a(b+c)=ab+ac
a(b+c)(d+e)=abd+abe+acd+ace (a+b)(c+d)=ac+ad+bc+bd
-(-a)=a


Fractions Rules

\frac{0}{a}=0 \: ,\: a\ne 0 \frac{a}{1}=a
\frac{a}{a}=1 (\frac{a}{b})^{-1}=\frac{1}{\frac{a}{b}}=\frac{b}{a}
(\frac{a}{b})^{-c}=((\frac{a}{b})^{-1})^{c}=(\frac{b}{a})^{c} a^{-1}=\frac{1}{a}
a^{-b}=\frac{1}{a^b} \frac{-a}{-b}=\frac{a}{b}
\frac{-a}{b}=-\frac{a}{b} \frac{a}{-b}=-\frac{a}{b}
\frac{a}{\frac{b}{c}}=\frac{a\cdot c}{b} \frac{\frac{b}{c}}{a}=\frac{b}{c \cdot a}
\frac{1}{\frac{b}{c}}=\frac{c}{b}


Absolute Rules

\left| -a \right| = \left| a \right| \left|a\right|=a \: ,\: a\ge0
\left| ax\right| = a \left| x\right| \: , \: a\ge 0


Exponent Rules

1^{a}=1 a^{1}=a
a^{0}=1\:,\: a\ne 0 0^{a}=0\:,\: a\ne 0
(ab)^n=a^{n}b^{n} \frac{a^m}{a^n}=a^{m-n}\:,\: m>n
\frac{a^m}{a^n}=\frac{1}{a^{n-m}}\:,\: n>m a^{b+c}=a^{b}a^{c}
(a^{b})^{c}=a^{b\cdot c} a^{bx}=(a^b)^x
(\frac{a}{b})^{c}=\frac{a^{c}}{b^{c}} a^c \cdot b^c=(a\cdot b)^{c}


Radical Rules

\sqrt{1}=1 \sqrt{0}=0
\sqrt[n]{a}=a^{\frac{1}{n}} \sqrt[n]{a^m}=a^{\frac{m}{n}}
\sqrt{a}\sqrt{a}=a \sqrt[n]{a^n}=a,\:a\ge0
\sqrt[n]{a^n}=|a|,\:\mathrm{n\:is\:even} \sqrt[n]{a^n}=a,\:\mathrm{n\:is\:odd}
\sqrt[n]{ab}=\sqrt[n]{a}\sqrt[n]{b},\:a,b\ge0 \sqrt[n]{\frac{a}{b}}=\frac{\sqrt[n]{a}}{\sqrt[n]{b}},\:a,b\ge0


Factor Rules

x^{2}-y^{2} = (x-y)(x+y)
x^{3}+y^{3} = (x+y)(x^{2}-xy+ y^{2})
x^{n}-y^{n} = (x-y)(x^{n-1}+x^{n-2}y+ \dots + xy^{n-2} + y^{n-1})
x^{n}+y^{n} = (x+y)(x^{n-1}-x^{n-2}y+ \dots - xy^{n-2} + y^{n-1}) \quad \quad \mathrm{n\:is\:odd}
ax^(2n)-b = (\sqrt{a}x^n+\sqrt{b})(\sqrt{a}x^n-\sqrt{b})
ax^(4)-b = (\sqrt{a}x^2+\sqrt{b})(\sqrt{a}x^2-\sqrt{b})
ax^(2n)-by^(2m) = (\sqrt{a}x^n+\sqrt{b}y^m)(\sqrt{a}x^n-\sqrt{b}y^m)
ax^(4)-by^(4) = (\sqrt{a}x^2+\sqrt{b}y^2)(\sqrt{a}x^2-\sqrt{b}y^2)


Factorial Rules

\frac{n!}{(n+m)!}=\frac{1}{(n+1)\cdot(n+2)\cdots(n+m)} \frac{n!}{(n-m)!}=n\cdot(n-1)\cdots(n-m+1), n>m
0!=1 n!=1\cdot2\cdots(n-2)\cdot(n-1)\cdot n


Log Rules

\log(1)=0 \log_a(a)=1
\log_{a}(x^b)=b\cdot\log_{a}(x) \log_{a^b}(x)=\frac{1}{b}\log_{a}(x)
\log_{a}(\frac{1}{x})=-\log_{a}(x) \log_{\frac{1}{a}}(x)=-\log_{a}(x)
\log_{a}(b)=\frac{\ln(b)}{\ln(a)} \log_{x}(x^n)=n
\log_{x}((\frac{1}{x})^{n})=-n a^{\log_{a}(b)}=b


Undefined

0^{0}=\mathrm{Undefined} \frac{x}{0}=\mathrm{Undefined}
\log_{a}(b)=\mathrm{Undefined}\:,\: a\le0 \log_{a}(b)=\mathrm{Undefined}\:,\: b\le0
\log_{1}(a)=\mathrm{Undefined}


Complex Number Rules

i^{2}=-1 \sqrt{-1}=i
\sqrt{-a}=\sqrt{-1}\sqrt{a}


We want your feedback

(optional)
(optional)

Please add a message.

Message received. Thanks for the feedback.


Cancel

Generating PDF...